Gender Gaps in Completed Fertility - Michèle Tertilt; Erica Field; Vera Molitor (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
The most commonly used measure of reproductive behavior is the total fertility rate (TFR), which is a measure of the number of children born per woman. However, almost no work exists measuring the fertility behavior of men. In this paper we use survey data from several recent waves of the Demographic and Health Surveys in six developing countries in which men and women were each asked about their reproductive histories. We document a number of interesting differences in fertility outcomes of men and women. First, while one might have thought that average rates for men and women must coincide, we find that this is not the case. Comparing completed fertility by birth cohorts, we find that on average men have more children than women in four out of the six countries we consider. The gaps are large reaching up to 4.6 children in Burkina Faso for the 1944 48 birth cohort. We show that positive gaps are possible when populations are growing and men father children with younger women. Such a situation often coincides with polygyny, i.e. men having children with more than one woman. Indeed we find that the size of the fertility gap is positively related to the degree of polygyny in the country. Second, we find a higher variance in fertility rates for men than for women. In other words, women are more similar to each other in reproductive behavior than men are to one another. Third, we find that differences in the desire to have children can largely be explained by differences in realized fertility. This implies that differences in fertility preferences often emphasized in the literature do not necessarily need to cause conflict, as men and women can realize their fertility individually. Finally, we find that for men, the demographic transition started earlier and was steeper than for women. These novel facts are useful when building theories of fertility choice.
Keywords: J13; J16; J10; 330